Protection and Care of Children Post Marriage Dispensation - Arhjayati Rahim; Noor Asma (Musamus Law Review, 2023)
his research examines and answers the forms of legal protection for children after the marriage dispensation and factors that influence the implementation of legal protection for children after the marriage dispensation in Gorontalo Province. This research is a type of empirical legal research which is descriptive analysis in nature. The data analysis technique uses qualitative descriptive analysis techniques. This analysis technique provides an overview of the logical flow of data analysis, as well as providing input on the qualitative data analysis techniques used. Forms of legal protection for children after marriage dispensation in Gorontalo Province are: Administrative Protection, Psychological Protection and Social Protection. Factors influencing the implementation of legal protection for children after the marriage dispensation in Gorontalo province: Internal factors and external factors. Internal factors include: Covering the Family's Shame and Disgrace Most of what influences the request for marriage dispensation, Preventing Adultery is Dominant is the reason put forward by the applicants. The two prospective bride and groom have been dating for a long time and are very close and difficult to separate so that the parents are afraid they will fall into the trap. to the act of Zina. External factors, namely: economic factors, educational factors, and social media which can be easily accessed via the internet, are gradually having a big influence on the interaction and social patterns of teenagers.